Are Brain–Computer Interfaces Feasible With Integrated Photonic Chips? - Salari, Vahid; Rodrigues, Serafim; Saglamyurek, Erhan; Simon, Christoph; Oblak, Daniel (Frontiers in Neuroscience, 2022)
The present paper examines the viability of a radically novel idea for brain-computer interface (BCI), which could lead to novel technological, experimental and clinical applications. BCIs are computer-based systems that enable either one-way or two-way communication between a living brain and an external machine. BCIs read-out brain signals and transduce them into task commands, which are performed by a machine. In closed-loop the machine can stimulate the brain with appropriate signals. In recent years, it has been shown that there are some ultraweak light emissions from neurons within or close to the visible spectra and near-infrared. Such ultraweak photon emission (UPE) reflects the cellular (and body) oxidative status, and compelling pieces of evidence are beginning to emerge that UPE may well play an informational role in neuronal functions. In fact, several experiments point to a direct correlation between neural activity, oxidative reactions, EEG activity, cerebral blood flow, cerebral energy metabolism, and release of glutamate with UPE intensity. Therefore, we propose a novel skull implant BCI that uses UPE. We suggest that an integrated photonic chip installed on the interior surface of the skull may enable a new form of extraction of the relevant features from the UPE signals. Nowadays, photonic technologies are getting dominant over electrical technologies, therefore photonic chips may have some advantage over electrical chips such as miniaturization, higher speed, low thermal effects, and large integration capacity that allow for high yield, volume manufacturing, and lower prices. In fact, we are making some very major conjectures, which need to be experimentally verified, and therefore we discuss the controversial parts, feasibility of technology and limitations, and potential impact of this envisaged technology if it can be successfully implemented in future.